The Effect of Using Geogebra Assisted STAD Type Learning Model on Problem Solving Ability and Mathematical Disposition - Hardika Saputra (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2022)
This study aims to analyze the effect of the geogebra-assisted STAD type cooperative learning model on improving geometric problem solving and mathematical disposition skills. The population in this study was the fifth grade students of SD Muhammadiyah Metro for the academic year 2021/2022 as many as 104 students spread into 3 classes. This study used quasi-experimental research with a non-equivalent pretest and posttest group design. With the sampling technique selected from 3 classes that have the same relative average math scores then taken randomly. Class V Ar Rahman was chosen as the class that uses cooperative learning type STAD assisted by geogebra and class V Al Haq as the class that uses direct learning. The data collection technique used a mathematical disposition test and questionnaire. Tests and questionnaires were given at the beginning of learning (pretest) and at the end of learning (posttest). After that the data were analyzed using the t-test formula. The results showed that students who received STAD cooperative learning with the help of geogebra had higher geometric problem solving abilities and mathematical dispositions than students who received direct learning. So it can be concluded that the application of geogebra-assisted STAD cooperative learning has an effect on increasing students' geometric problem solving abilities and mathematical dispositions